(3OQGSI fbOjIs - (3GHQGgje CMeO(B, (3NdjaIs ((3GdGScfOQjI(B:s (3OGQ GdLGeYI GdLOjOI(B,s, 2008)
(3CgOGa efXeI GdJLGQI GdYGdejI h eHGOFgG h GdYVhjI aj efXeI GdJLGQI GdYGdejI h GNJUGUGJ efXeI GdJLGQI GdYGdejI h fWGb YedgG eY JfGhd GdHfGA GdJfXjej defXeI GdJLGQI GdYGejI h ejRGfjI gPg GdefXeI h GdTNUjI GdbGfhfjI dgG h CMcGe EUOGQ GdbQGQGJ ajgG h GdQhQ GdQbGHj dgG h GNjQG MOhO ENJUGU efXeI GdJLGQI GdYGdejI(B.s
(3edGMb U(B.193 (3eQGLY U(B.265s
Keywords: (3GdJLGQI GdNGQLjIs; (3GdefXeGJ GdOhdjIs; (3efXeI GdJLGQI GdYGdejIs